An algorithm to assess the heating strategy of buildings in cold climates: a case study of Germany. (22nd March 2022) - Mazhar, Abdur Rehman; Zou, Yuliang; Zeng, Cheng; Shen, Yongliang; Liu, Shuli
Abstract: Two-thirds of the final energy consumption of the EU residential sector goes towards space heating of buildings, yet a huge portion of the population still suffers from energy poverty. Identifying optimum heating strategies of current buildings would be a solution to this crisis, which is the main aim of the developed algorithm in this research. The algorithm incorporates a modified version of the simple hourly method from the ISO 13790 standard to determine the hourly heating load and indoor temperatures of buildings based on any heating strategy. Flexibility in the input of building and weather data make this tool versatile with practicality towards building users and policymakers. With this algorithm, a case study to evaluate three commonly used domestic heating strategies has been established for nine different residential buildings in typical cold winter conditions in Germany. Most EU households heat their buildings either continuously throughout the day at fixed temperatures, sporadically at fixed times or at peak loads during the evening. The continuous heating strategy is rated the best consuming minimal energy with consistent temperatures and optimal thermal comfort ranges. The sporadic and peak load heating strategies provide fluctuating indoor temperatures with high standard deviations of up to 8.70°C while consuming a similar cumulative energy to the continuous heating strategy. Additionally, both these aforementioned strategies augment energy poverty and promote indoor mould formation on the building envelope caused by water vapor condensation. Consequently, this algorithm can be applicable to any building type of any region.